Environmental Management at Star Rated Hotel in Bali - Pramono, Jaya; Budi Susrusa, I Ketut; Wiranatha, Agung Suryawan (E-Journal of Tourism, 2014)
The outcomes of tourism in relation to the environmental sustainability is to preserve nature, environment, and resources availablity. Therefore, the obligation to maintain sustainability of environmental are become a top agenda for the managers of the star-rated hotels. In line with this spirit the high growth of hotel and tourist arrival in Bali correlated with the high of resources use to meet the demand of hotel guests, it will affect to the environment of hotel and the environmental of Bali. This study surveyed 126 star hotels in Bali (which consists of four (4) one-star hotels, ten (10) two-star hotels, thirty-nine (39) three-star hotels, twenty-four (24) four-star hotels, and forty-nine (49) five star hotels, using a questionnaire, where the alternative answer used the seven (7) options, and the data were analyzed using descriptive statistics, and structural equation modelling (SEM). This study successfully established a significant model that describes the relationship between environmental issues, environmental management processes, and the benefits of environmental management processes in star rated hotels in Bali. Also the results of this research demonstrate that: 1. There is a significant relationship between environmental issues to the process of environmental management at star rated hotels in Bali, and 2. There is a significant relationship between the process of environmental management to the the benefits of environmental management processes of the star rated hotels in Bali. Furthermore, the issues of environment is consists of: a. The issue of pressure from tour operator, b. The issue of customer and tourists pressure, and c. The issue of climate change. Then the environmental management process of hotel consists of: a. The wastewater management process, b. The solid waste management processes, and c. The chemical management processes, and finally the benefits of environmental management processes in star hotels are consists of: a. The sustaining the hospitality industry, b. The contribution to community development, and c. The satisfaction of the guests at star rated hotels in Bali. In accordance with these results is it suggested that every hotels are encouraged to do the process of environmental management because through this process, hotel will have a better relationship with the community, it had the preferred of tourists trend, it had became more prudent in term of resources use as a sustainable environmental efforts, and finally these can contribute to preserving the assets of the world for future generations.
Keywords: environmental management, star-rated hotel, Bali